Advancements in Facial Recognition Technology for Early Detection of Down Syndrome in Children: Facial Recognition Technology for Early Detection of Down Syndrome (Academic Journal of International University of Erbil, 2025)
Artificial intelligence and facial recognition have opened new avenues for early detection of even genetic conditions. This research paper applies a state-of-the-art object detection model, YOLOv8, to accurately identify children with Down syndrome from their faces. The model is then trained and fine-tuned on the face image dataset for high-performance metrics not seen earlier, using the real-time detection capability of YOLOv8.The model was precision at 0.958 and had a high recall at 0.967. That means that the model will mostly correctly identify all children with Down syndrome while keeping the false positives and false negatives to the minimum. Also, the mean Average Precision of the model is 0.988 out of 1.00 on the IoU threshold of 0.50, mAP50, showing near-perfect overlap between predicted and actual face regions. The model also maintained high performance at 0.746 mAP50-95, which informs the model's ability to make more accurate predictions over the stricter IoU thresholds.These findings suggest that YOLOv8 may be employed for effective early screening for Down syndrome, offering healthcare providers a non-invasive and efficient solution. More robust detection performance about relevant facial features indicative of the condition will support early diagnosis and, therefore, timely interventions that will significantly enhance the quality of life in children affected with Down syndrome.This study is probably the most noninvasive, inexpensive screening method for Down syndrome in the world. Its availability can help the least developed parts of the world intervene as early as possible and improve the outcomes for children worldwide, especially those from the most deprived areas.